Małgorzata Szumowska – a Few Scenes from a Filmmaker’s Life (2000-2008) - Pławuszewski, Piotr (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2012)
Małgorzata Szumowska – her strong position during the last decade in the history of Polish cinema seems unquestionable. Speaking with her own, original voice, she has successfully refused to be pigeonholed. The only thing one can be sure of in reference to Małgorzata Szumowska is that she will keep moving forward artistically. The main goal of the article is to examine this interesting journey, following selected threads, in particular, the need for love and facing death or a serious illness, in Szumowska’s filmography over the last decade.

Mocna pozycja, jaką wypracowała sobie w ciągu ostatnich kilkunastu lat Małgorzata Szumowska w polskim kinie,  trudna jest do zakwestionowania. Przemawiając własnym, oryginalnym głosem, udanie ucieka do jakichkolwiek zaszufladkowań. Artykuł stanowi próbę krótkiego podsumowania dotychczasowych poczynań filmowych Małgorzaty Szumowskiej, ze szczególnym wskazaniem na dwa powracające w ramach tej twórczości wątki: potrzebę miłości oraz mierzenie się z widmem śmierci/poważnej choroby.
Małgorzata Szumowska - Kilka scen z życia filmowca (2000-2008)
Piotr Pławuszewski, Katedra Filmu, Telewizji i Nowych Mediów UAM, Małgorzata Szumowska - Kilka scen z życia filmowca (2000-2008), Małgorzata Szumowska – a Few Scenes from a Filmmaker’s Life (2000-2008), „Images” 2012, vol. XI: (Re)imagining the Past, red. A. Mrozewicz i J. Czaja, nr 20, s. 212-216., ISSN 1731-450X, język: angielski
Keywords: Szumowska; autobiographical; family; death; illness; feature film; documentary; autobiograficzny; rodzina; śmierć; choroba; film fabularny; film dokumentalny